Negative inotropic effects of tumour necrosis factor-α and interleukin-1β are ameliorated by alfentanil in rat ventricular myocytes - Duncan, D J (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Serum levels of tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) increase during an inflammatory response and have been reported to induce a negative inotropic effect on the myocardium. Alfentanil, an opioid analgesic often used in the critical care of patients with sepsis, has been shown to enhance ventricular contractility. This study characterised the effects of TNF-α and IL-1β on contraction and the Ca(2+) transient and investigated whether depressed ventricular function was ameliorated by alfentanil. EXPERIMENTAL APPROACH: Isolated rat ventricular myocytes were loaded with fura-2 and electrically stimulated at 1 Hz. Contraction and Ca(2+) transients were measured after 60, 120 and 180 min incubations in TNF-α (0.05 ng ml(−1)) and IL-1β (2 ng ml(−1)). The effects of 10 μM alfentanil on contractility and Ca(2+) transients of TNF-α and IL-1β treated cells were determined. KEY RESULTS: After 180 min of TNF-α and IL-1β treatment, the amplitude of contraction, the Ca(2+) transient and sarcoplasmic reticulum (SR) Ca(2+) content were significantly reduced. Alfentanil significantly increased contraction of TNF-α and IL-1β treated cells via a small increase in the Ca(2+) transient and a larger increase in myofilament Ca(2+) sensitivity, effects that were not blocked by 10 μM naloxone, a broad spectrum opioid receptor antagonist. CONCLUSIONS AND IMPLICATIONS: TNF-α and IL-1β induce a significant negative inotropic effect on ventricular myocytes in a time dependent manner through disruption of SR Ca(2+) handling and the Ca(2+) transient. This negative inotropic effect was ameliorated by alfentanil, but this response may not be mediated via opioid receptors.